BIOLOGICAL AND ECOLOGICAL FEATURES AND ECONOMIC IMPORTANCE OF TRIBULUS TERRESTRIS L. GROWING IN KARAKALPAKSTAN - Ajiev, Alisher Bakhtibayevich; Perdebayeva, Gulasal Askarovna (SCIENCE and SOCIETY, 2026)
This study investigates the biological, ecological and economic characteristics of Tribulus terrestris L., a medicinal plant naturally distributed in the Republic of Karakalpakstan. Morphological and anatomical characteristics, ecological distribution, habitat conditions, chemical composition and medicinal properties of the species were evaluated based on field observations and scientific literature. The findings indicate that T. terrestris is well adapted to arid and saline environments and contains significant amounts of biologically active compounds, including steroidal saponins, flavonoids and alkaloids. The obtained results demonstrate the importance of this species for pharmaceutical production, traditional medicine, biodiversity conservation and sustainable utilization of natural plant resources.
Keywords: Tribulus terrestris L.; medicinal plant; bioecology; flavonoids; steroidal saponins; Karakalpakstan